2022
DOI: 10.1111/ijfs.16079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wet milling on the properties of highland barley flour and the quality of highland barley bread

Abstract: Summary To explore the effects of wet milling method on highland barley flour and highland barley bread, we investigated the characteristics of highland barley flours and the quality of highland barley breads made from whole grain highland barley flour (WGBF), dry‐milled highland barley flour (DBF) and wet‐milled highland barley flour (WBF). Compared to other highland barley flours, WBF had lower damaged starch content (1.37 g/100 g), higher pasting temperature and higher gel strength. In addition, WBF with la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In general, DBD‐ACP treatment had a positive effect on water hydration properties while reducing the thermal stability of whole grains flours. The results showed that WAI, WSI and SP values were 3.45 g/g, 16.97% and 5.04 g/g for WQ, 4.27 g/g, 12.88% and 5.34 g/g for WHB, 4.01 g/g, 16.29% and 4.29 g/g for WT, respectively, which aligned with several previous studies (Contreras‐Jimenez et al ., 2019; He et al ., 2022). Compared with WQ, WHB and WT, the WAI values of WQ 10 , WQ 20 , WHB 10 , WHB 20 , WT 10 and WT 20 increased by 20.58%, 17.68%, 6.32%, 19.91%, 20.45% and 12.97% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In general, DBD‐ACP treatment had a positive effect on water hydration properties while reducing the thermal stability of whole grains flours. The results showed that WAI, WSI and SP values were 3.45 g/g, 16.97% and 5.04 g/g for WQ, 4.27 g/g, 12.88% and 5.34 g/g for WHB, 4.01 g/g, 16.29% and 4.29 g/g for WT, respectively, which aligned with several previous studies (Contreras‐Jimenez et al ., 2019; He et al ., 2022). Compared with WQ, WHB and WT, the WAI values of WQ 10 , WQ 20 , WHB 10 , WHB 20 , WT 10 and WT 20 increased by 20.58%, 17.68%, 6.32%, 19.91%, 20.45% and 12.97% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As found by del Carmen Robles‐Ramirez et al ., 4 bread produced by replacing wheat flour with barley flour has higher nutritional value, including higher fiber, phenolic compounds, and antioxidant activity. Also, He et al 5 . reported that the content of dietary fiber in HBF was higher than that in whole wheat flour.…”
Section: Introductionmentioning
confidence: 99%
“…3 As found by del Carmen Robles-Ramirez et al, 4 bread produced by replacing wheat flour with barley flour has higher nutritional value, including higher fiber, phenolic compounds, and antioxidant activity. Also, He et al 5 reported that the content of dietary fiber in HBF was higher than that in whole wheat flour. However, the unfavorable processing properties of industrial HBF had a great impact on the texture and edible qualities of highland barley bread (HBB).…”
Section: Introductionmentioning
confidence: 99%